Default mode network connectivity change corresponds to ketamine's delayed glutamatergic effects - Li, Meng; Woelfer, Marie; Colic, Lejla; Safron, Adam; Chang, Catie; Heinze, Hans Jochen; Speck, Oliver; Mayberg, Helen S.; Biswal, Bharat B.; Salvadore, Giacomo; Fejtová, Anna; Walter, Martin (European archives of psychiatry and clinical neuroscience, 2018)
Ketamine exerts rapid antidepressant effects peaking 24 h after a single infusion, which have been suggested to be reflected by both reduced functional connectivity (FC) within default mode network (DMN) and altered glutamatergic levels in the perigenual anterior cingulate cortex (pgACC) at 24 h. Understanding the interrelation and time point specificity of ketamine-induced changes of brain circuitry and metabolism is thus key to future therapeutic developments. We investigated the correlation of late glutamatergic changes with FC changes seeded from the posterior cingulate cortex (PCC) and tested the prediction of the latter by acute fractional amplitude of low-frequency fluctuations (fALFF). In a double-blind, randomized, placebo-controlled study of 61 healthy subjects, we compared effects of subanesthetic ketamine infusion (0.5 mg/kg over 40 min) on resting-state fMRI and MR-Spectroscopy at 7 T 1 h and 24 h post-infusion. FC decrease between PCC and dorsomedial prefrontal cortex (dmPFC) was found at 24 h post-infusion (but not 1 h) and this FC decrease correlated with glutamatergic changes at 24 h in pgACC. Acute increase in fALFF was found in ventral PCC at 1 h which was not observed at 24 h and inversely correlated with the reduced dPCC FC towards the dmPFC at 24 h. The correlation of metabolic and functional markers of delayed ketamine effects and their temporal specificity suggest a potential mechanistic relationship between glutamatergic modulation and reconfiguration of brain regions belonging to the DMN.
EVALuna2:211604